Multi-Degree-of-Freedom Stretchable Metasurface Terahertz Sensor for Trace Cinnamoylglycine Detection - Huanyu Li; Wenyao Yu; Mengya Pan; Shuo Liu; Wanxin Nie; Yifei Zhang; Yanpeng Shi (Biosensors)
Terahertz (THz) spectroscopy, an advanced label-free sensing method, offers significant potential for biomolecular detection and quantitative analysis in biological samples. Although broadband fingerprint enhancement compensates for limitations in detection capability and sensitivity, the complex optical path design in operation restricts its broader adoption. This paper proposes a multi-degree-of-freedom stretchable metasurface that supports magnetic dipole resonance to enhance the broadband THz fingerprint detection of trace analytes. The metasurface substrate and unit cell structures are constructed using polydimethylsiloxane. By adjusting the sensor’s geometric dimensions or varying the incident angle within a narrow range, the practical optical path is significantly simplified. Simultaneously, the resonance frequency of the transmission curve is tuned, achieving high sensitivity for effectively detecting cinnamoylglycine. The results demonstrate that the metasurface achieves a high-quality factor of 770.6 and an excellent figure of merit of 777.2, significantly enhancing the THz sensing capability. Consequently, the detection sensitivity for cinnamoylglycine can reach 24.6 µg·cm−2. This study offers critical foundations for applying THz technology to biomedical fields, particularly detecting urinary biomarkers for diseases like gestational diabetes.